Exploring indigenous Bacillus spp. as a biostimulant to enhance the growth and yield of rice under glasshouse conditions (Asian Journal of Agriculture, 2025)
Abstract. Shultana R, Zuan ATK, Rana MM, Naher UA, Paul PLC, Akter M, Shupta SA, Roy TK. 2025. Exploring indigenous Bacillus spp. as a biostimulant to enhance the growth and yield of rice under glasshouse conditions. Asian J Agric 9: 131-139. Plant growth-promoting rhizobacteria (PGPR) appeared as an emerging approach to sustainable agriculture because of their ability to reduce the need for synthetic fertilizers. This study evaluated five potential Bacillus strains isolated from rice-growing areas in northern Malaysia for their ability to enhance rice growth parameters under laboratory and glasshouse conditions. Among the five strains, two UPMRB9 (Bacillus tequilensis 10b) and UPMRE6 (Bacillus aryabhattai B8W22) exhibited all the desired traits. These strains were subsequently inoculated into three potential rice plants, resulting in improved morphological (plant height, leaf area), physiological (photosynthesis, transpiration, stomatal conductance, dry biomass, and grain yield), and biochemical (total chlorophyll, total proline content, total soluble sugar, and uptake of N, P, K, Ca, and Mg) attributes. Inoculation of Putra-1 plants with UPMRB9 showed a 10.76% increase in plant height, a 50.82% increase in grain yield, a 12.32% increase in colonization, and a 56% increase in stomatal conductance. Additionally, inoculation of BRRI dhan67 with UPMRB9 reduced the transpiration rate by 100.89%. MR297 plants treated with UPMRB9 demonstrated an 86.58% increase in leaf area, a 125.81% increase in photosynthesis, a 222.19% increase in dry biomass, a 56.03% increase in total chlorophyll, a 62.93% increase in proline content, and a 62.93% increase in total soluble sugar (TSS). Therefore, UPMRB9, as a multiple plant growth promoter, could be an alternative to synthetic fertilizers for rice cultivation.
Keywords: Bacillus, biofertilizer, nutrient uptake, PGPR, proline